2007
DOI: 10.1097/mao.0b013e31814b2285
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Expression and Histopathologic Features in Vestibular Schwannomas

Abstract: Cyclin D1 expression, present in nearly half of the cases, may play a role in the development of these tumors. Further studies are needed to fully understand the contributions of histopathologic and immunohistochemical factors to vestibular schwannoma biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Our goal, with the help of new improved tools for data analysis, was to perform a more thorough analysis of the expression patterns of 31 schwannomas and 9 controls. Our results concur with earlier array analysis data on schwannomas, such as caveolin-1 (CAV1) downregulation (25), as well as with other studies conducted, using techniques such as qRT-PCR [i.e., neuregulin 1 (NRG1)-ErbB2-ErbB3 upregulation] and immunohistochemistry analysis (CCND1 upregulation) (26). …”
Section: Introductionsupporting
confidence: 92%
“…Our goal, with the help of new improved tools for data analysis, was to perform a more thorough analysis of the expression patterns of 31 schwannomas and 9 controls. Our results concur with earlier array analysis data on schwannomas, such as caveolin-1 (CAV1) downregulation (25), as well as with other studies conducted, using techniques such as qRT-PCR [i.e., neuregulin 1 (NRG1)-ErbB2-ErbB3 upregulation] and immunohistochemistry analysis (CCND1 upregulation) (26). …”
Section: Introductionsupporting
confidence: 92%
“…Patients with positive cyclin D1 expression had better facial function outcome. In a previous study, we found an association between cyclin D1 expression and cellular degenerative changes (8). As these changes may reflect long-term, that is, less aggressive lesions, this could explain why overexpression of a proto-oncogen is associated with a favorable facial outcome.…”
Section: Discussionmentioning
confidence: 78%
“…Immunohistochemical cyclin D1 expression has been recently described in 52% of 22 patients with VS. Cyclin D1 expression was more frequent in tumors with nuclear degenerative changes, as well as in patients with longer duration of deafness and higher (2,000 Hz) hearing thresholds (8).…”
mentioning
confidence: 99%
“…Cyclin D1 is a cell-cycle regulatory protein for the mammalian G1-S phase transition and is implicated in cell proliferation and differentiation. Lassaletta et al [85] found, using immunohistochemistry, cyclin D1 expression in 52% of their cases. This deregulated gene was more frequently present in tumors with nuclear degenerative changes (Figure 1).…”
Section: Deregulated Genes In Vestibular Schwannomamentioning
confidence: 99%